WORD FORMATION PROCESSES OF REGISTERS USED IN DUNIAFITNES.COM NEWSLETTER - FAHMAWATI, YARI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Human being as an individual and social creature cannot communicate or interact with other people without using language as an instrument. Language not only functions as a communication tool, but also functions as a special feature from the social existence. Language and society are inseparable and therelationship could be seen through the effects of social factors on language and the society. People’s social behavior in society can be reflected through theexpression of their idea and feelings. Language exists in a number of varieties,such as dialect, style, slang, register, etc. Registers are sets of language itemsassociated with discrete occupational or social groups. Register may occur both inone language such as utterances, public-speech, or conversation and writtenlanguage such as article, editorial book and literature. In this study, the writer investigates register in written language, pricisely the newsletter Duniafitnes.com Newsletter because in written text the writer can find and analyze the register variables clearly. From the fitness registers, the writer analized the word formation processes that include one of morphology aspect. The problems of this study are (1) What are the registers found in Duniafitnes.com Newsletter? (2) What are the word formation processes found in the registers of Duniafitnes.com Newsletter?In this study, the writer is interested in analyzing word formation processes of fitness registers since word formation processes is the study of the process which is new words come into being a language (Yule, 2006). This study is aimed to investigate the the registers and meaning, and the words formationprocesses found in the registers of Duniafitnes.com Newsletter from January untilApril 2013. The writer uses Yule’s theory (2006) to analyze the data.This study used descriptive qualitative approach. The result of the studyare 40 fitness registers found in Duniafitnes.com Newsletter. The word formationof fitness registers are Borrowing (40 terms), Multiple Processes (12 terms),Compounding (10 terms), Acronym (1 term) and Derivation (1 term). The writerfound that Borrowing is the most dominant process used.The result of the study is expected to give significance to the nextresearchers who are interested in studying the same area. to take another popular sports beside fitness that might find the registers. Keywords: word formation processes, registers, newsletter.